exploring the relationship between various testing-methods and heart rate durring judo matches - ben aicha, alaa el dine Nouali yasser alaae eddine (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
Abstract Objective: To investigate the relationship between different testing methods and heart rate in judo athletes During Judo Matches. Methods: Eight lightweight (<66 kg and <73 kg) University Division I judoka were tested (mean age: 21±1.06 years; height: 171±6.84 cm; weight: 69±5.59 kg; years of training: 10±2 years). Each athlete performed a 10-second continuous over-the-shoulder wrestling attack, a crucifixion run, a 150-meter speed run, and a 90-second attack test to compare anaerobic heart rate responses during judo-specific competition training. Data were analyzed using Pearson's cumulative correlation and repeated measures ANOVA. Results: The 150m sprint was significantly correlated with the 90-second judo test (r²=0.5). The coordination test showed a moderate correlation with the judo-specific test (r²=0.3). The judo UKSN was strongly correlated with the coordination test (r²=0.7) but not with the 3m cross run (r²=0.1). Conclusion: The four-limit analysis model highlights the strengths and weaknesses of athletes' basic and specialized abilities. Poor basic abilities in judo can impact performance in specialized sports. Future training should focus on strengthening identified weaknesses using the four-limit analysis model to predict basic abilities during the preparatory training period. // // // // // Résumé de l’étude Objectif : Étudier la relation entre les différentes méthodes de test et la fréquence cardiaque chez les athlètes de judo lors des matchs de judo. Méthodes : Huit judokas légers (<66 kg et <73 kg) de Division universitaire I ont été testés (âge moyen : 21 ± 1,06 ans ; taille : 171 ± 6,84 cm ; poids : 69 ± 5,59 kg ; années d'entraînement : 10 ± 2 ans). ). Chaque athlète a effectué une attaque continue de lutte par-dessus l'épaule de 10 secondes, une course de crucifixion, une course de vitesse de 150 mètres et un test d'attaque de 90 secondes pour comparer les réponses de la fréquence cardiaque anaérobie au cours d'un entraînement de compétition spécifique au judo. Les données ont été analysées à l'aide de la corrélation cumulative de Pearson et de l'ANOVA à mesures répétées. Résultats : Le sprint de 150 m était significativement corrélé au test de judo de 90 secondes (r²=0,5). Le test de coordination a montré une corrélation modérée avec le test spécifique au judo (r²=0,3). L'UKSN de judo était fortement corrélé au test de coordination (r²=0,7) mais pas à la course croisée de 3 m (r²=0,1). Conclusion : Le modèle d'analyse à quatre limites met en évidence les forces et les faiblesses des capacités de base et spécialisées des athlètes. De mauvaises capacités de base en judo peuvent avoir un impact sur les performances dans les sports spécialisés. La formation future devrait se concentrer sur le renforcement des faiblesses identifiées en utilisant le modèle d'analyse à quatre limites pour prédire les capacités de base au cours de la période de formation préparatoire.
LES-2024-13
Keywords: : Judo training - 3m cross running- coordination // // Entraînement de judo- course cross 3m- coordination